Maple leaf shaped array antenna for multiband applications - Vasujadevi, M; T P Madhav, B; Shiva Skandan, A; Rajeswari, P; Arjun Rao, K; Khyathi Reddy, K; Vekateswara Rao, M (International Journal of Engineering and Technology, 2017)
This article presents design and analysis of maple leaf shaped array antenna for high gain applications. The proposed antenna is characterized and analyzed using ANSYS EM desktop 17. This antenna works at 2.17-2.54(S band),5.3-5.64, 6.91-7.80(C Band), 8.76-9.15(X band), 12.49-12.75, 14.78-16.65(Ku band). The bands of the proposed antenna has its applications at LTE 2.3 GHz, ISM 2.4 GHz, WLAN, ISM, Bluetooth at S-band and upper WLAN at C-band, Military applications and air traffic control at X-band. This single antenna dimensioned 21x18x1.6 mmÂ³ is later arrayed in 1x4. This antenna has peak gain at 7.8dB and the average gain of 4.2dB. The proposed 1x4 array antenna is characterized and obtained return loss, gain, E field, current distribution and far field radiation patterns.
Keywords: Maple leaf; ANSYS EM desktop 17; return loss; gain; E field; current distribution; far field radiation patterns